Teaching English in the Age of Social Media: Challenges and Innovations - Himatur Rosida; Yeni Rahmawati; Sunarti (SOSIOEDUKASI, 2025)
This study explores using social media as an innovative tool for teaching English in resource-limited secondary schools. In the face of technological disparities and limited educational resources, particularly in underfunded or remote areas, integrating platforms such as WhatsApp, YouTube, Instagram, and TikTok presents an engaging and accessible approach to enhance English language instruction. Using a mixed-methods design, data were collected through questionnaires, interviews, and classroom observations involving English teachers and students in Samarinda, Indonesia. Findings show that social media increases student motivation, participation, and comprehension through authentic content and multimodal interaction. Teachers observed that learners responded positively to creative, structured activities delivered via social platforms. However, significant challenges were identified, including unequal access to the internet and devices, digital distractions, and insufficient teacher training in educational technology. Despite these barriers, both teachers and students acknowledged the potential of social media to enrich the language learning process when supported by effective instructional strategies. The study recommends teacher training on digital pedagogy, infrastructure improvement, and the development of clear guidelines for integrating social media into formal education. Ultimately, the research contributes valuable insights into how familiar digital tools can support English language learning in contexts where traditional resources are scarce